Las tecnologías de la información en la didáctica de los docentes de educación primaria de la IE Santísima Trinidad – Lima Cercado 2018 - Hirata Tejada, Luis Toribio (2019)
Objective: Determine the incidence of information technologies in the teaching of primary school teachers of the Holy Trinity School - Lima Cercado 2018. The type of study is non-experimental, Material and Method: The study design is causal correlation and the applied research method was the hypothetico-deductive one. Regarding the instruments that were used were Likert scale questionnaires for the variables information and didactics technologies. The aforementioned instruments were subjected to the respective reliability and validity analyzes, which determined that the questionnaires have validity and reliability. The population consisted of 80 teachers from the three levels of the Holy Trinity Hierarchy - Lima Cercado 2018. Results: The incidence of information technologies in the teaching of primary education teachers of the Holy Trinity School - Lima Cercado 2018. It was using ordinal logistic regression = .000 (high), with significance level less than 5% of standard significance, demonstrating that the hypothesis of the investigation is accepted and the null hypothesis is rejected. The level that predominates in the variable information technologies are presented 25% (20) that indicated Not acceptable, 60% (48) indicated Acceptable and 15% (22) indicated Good; unlike the variable the didactics are presented 45% (36) that indicated Not acceptable, 30% (24) indicated Acceptable and 25% (20) indicated Good. Conclusions: The information technologies in the didactics are of great importance in the teaching-learning process, in this sense in the Holy Trinity - Lima Cercado it is observed that there is a significant incidence between the information technologies and the didactics, with a coefficient of Wald = 9,752 and a sig value = 0,038 which indicates that the higher the use of information technologies, the didactics of primary school teachers in said institution will be good, since students will have a quality education